Pengaruh Lingkungan Kerja dan Work-Life Balance terhadap Kepuasan Kerja - Nur Ahmad Sabid; Agustina Fitrianingrum (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the influence of work environment and work-life balance on job satisfaction among employees in the city of Semarang. It seeks to identify key factors that enhance job satisfaction, especially among young and productive-age workers in an urban context. Methodology/approach: Using a quantitative approach, this research surveyed 160 respondents in Semarang through structured questionnaires employing a Likert scale. The respondents were selected via purposive sampling and represented diverse backgrounds in age, gender, and education. Data were analyzed using SmartPLS software to determine the significance and strength of the relationships between variables. Results/findings: The study reveals that both the work environment and work-life balance have a significant and positive effect on job satisfaction. A supportive and comfortable work environment boosts motivation and loyalty among employees. Meanwhile, a well-maintained work-life balance helps reduce work-related stress and improves employee retention. Most respondents are from the productive age group and have secondary-level education, influencing their perception of satisfaction levels. Conclusion: Work environment and work-life balance significantly influence job satisfaction. Enhancing these two aspects can lead to more motivated, loyal, and satisfied employees. Limitations: The study is geographically limited to Semarang and does not consider other variables such as leadership style or organizational culture, which may also affect job satisfaction. Contribution: This study contributes to the field of human resource management by offering insights into factors influencing job satisfaction in urban Indonesian settings. It is relevant for HR professionals, managers, and policymakers focused on improving employee engagement and organizational performance.